2020
DOI: 10.1097/md.0000000000021454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tenofovir antiviral treatment on survival of chronic hepatitis B related hepatocellular carcinoma after hepatectomy in Chinese individuals from Qingdao municipality

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…With antiviral treatments, the prognosis was comparable between patients with HBV loads <2000 IU/mL and those with HBV loads ≥2000 IU/mL after undergoing hepatectomy for early-stage HBV-related HCC. 24 For HCC patients receiving sorafenib, antiviral treatments could eliminate the adverse impacts of high HBV loads on survival. 25 Peter et al found that antiviral therapy can provide benefits for HCC patients in terms of survival, liver function and adverse events.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…With antiviral treatments, the prognosis was comparable between patients with HBV loads <2000 IU/mL and those with HBV loads ≥2000 IU/mL after undergoing hepatectomy for early-stage HBV-related HCC. 24 For HCC patients receiving sorafenib, antiviral treatments could eliminate the adverse impacts of high HBV loads on survival. 25 Peter et al found that antiviral therapy can provide benefits for HCC patients in terms of survival, liver function and adverse events.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…A Chinese study of 233 patients with CHB-related compensated cirrhosis showed that TDF treatment led to significantly longer disease-free survival compared to ETV treatment after liver resection (33 months for TDF and 24 months for ETV, P <0.001) [ 26 ]. Another study from China also reported that TDF treatment was associated with a significantly lower rate of HCC recurrence (aHR, 0.67; 95% CIs, 0.48–0.93; P =0.04) after liver resection compared to non-TDF treatment, such as ETV [ 27 ].…”
Section: Tenofovir Is Better Than Entecavir For the Prevention Of Hccmentioning
confidence: 99%
“…Regarding the tertiary prevention of HCC after curative treatment, there are a few studies comparing the effectiveness of ETV and TDF in preventing HCC recurrence. A Chinese study including 233 patients with HBV-related HCC who underwent liver resections observed that TDF treatment was associated with a significantly longer disease-free survival compared with ETV (33 months vs. 24 months, respectively; P < 0.001) [21] . Another study from China including 479 patients with HBV-related HCC confirmed this finding that TDF treatment was superior to non-TDF treatment including ETV (aHR = 0.67; 95%CI: 0.48-0.93; P = 0.04) in preventing HCC recurrence after curative resection [22] .…”
Section: Studies Showing the Superiority Of Tdf In Tertiary Prevention Of Hccmentioning
confidence: 99%